The turtle who fell off the stick - Robbins; Rita (Jamaica Mind to Mind, 2016)
Once, two geese and a turtle lived by a pond. One year, it was very hot and there was no rain$1! =(BThis book is printed in large print and beautiful page design. Read till the last page and learn the moral values behind this story.s